Program Yuk Nabung Saham terhadap Minat Investasi pada Kelompok UKM di Kota Medan Sumatera Utara - Liana, Vega; Silalahi, Purnama Ramadani; Ayuni, Putri; Syahputra, Rifandi (As-Syirkah: Islamic Economic & Financial Journal, 2023)
Let's invest in SME organizations in Medan, North Sumatra, and save stock for investment interest. The purpose of this study was to determine the influence of the "Yuk Saving Stock" program on SME investment interest in Medan, North Sumatra. In this study, the survey method was chosen as a research method. by gathering both primary and secondary information. Purposive sampling was used to choose the study site, and the t-test with simple linear regression was used to assess the results. The results show that the size of the independent variable fraction (x) explaining the Y variable may be determined using the correlation coefficient and determination coefficient. The strong and unidirectional relationship between savings shares and investment interests in Medan City UKM is indicated by the correlation value of 0.827. The percentage of shares that may explain the variable investment interest has a coefficient of determination of variation of 0.827, or 82.7 percent; the remaining 13.7 percent is explained by other variables not examined in this study.